CLIMATE CHANGE A REPERCUSSION OF HUMAN INDUCED SYSTEMS - Shweta Chand (Zenodo, 2021)
Climate change includes both the global warming driven by human emissions of greenhouse gases, and the resulting large-scale shifts in weather patterns. Though there have been previous periods of climatic change, since the mid-20th century, humans have had unprecedented impact on Earths climate system and caused change on a global scale.The largest driver of warming is the emission of greenhouse gases, of which more than 90% are carbon dioxide and methane. Fossil fuel burning (coal, oil, and gas) for energy consumption is the main source of these emissions, with additional contributions from agriculture, deforestation, and industrial processes. The human cause of climate change is not disputed by any scientific body of national or international standing. Temperature rise is accelerated or tempered by climate feedbacks, such as loss of sunlight-reflecting snow and ice cover, increased water vapour (a greenhouse gas itself), and changes to land and ocean carbon sinks.Temperature rise on land is about twice the global average increase, leading to desert expansion and more common heat waves and wildfires. Increasing rates of evaporation cause more intense storms and weather extremes. Temperature rise is amplified in the Arctic, where it has contributed to melting permafrost and the retreat of glaciers and sea ice. Additional warming also increases the risk of triggering critical thresholds called tipping points. Impacts on ecosystems include the relocation or extinction of many species as their environment changes, most immediately in coral reefs, mountains, and the Arctic. Human impacts include undernutrition and hunger from reduced crop yields, declining fish stocks, increases in vector-borne diseases, potentially severe economic impacts, increased global economic inequality, more people living in uninhabitable climate zones, and increased migration.Effects such as these have led the World Health Organization to declare climate change the greatest threat to global health in the 21st century. Even if efforts to ...